2013
DOI: 10.5455/njppp.2013.3.109-114
|View full text |Cite
|
Sign up to set email alerts
|

Difference in pulmonary function test among the athletic and sedentary population

Abstract: Background: Pulmonary function assessment has achieved a lot of importance nowadays owing to a steep rise in air pollution. Lung function parameters tend to have a relationship with lifestyle such as regular exercise and non-exercise. Hence the present study was under taken to assess the effects of exercise in athletes on respiratory system and compared with sedentary group. Aims & Objective: To compare the differences in pulmonary function test among the athletes and sedentary group. Materials and Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…These effects of vitamin D may be mediated through surfactant, a substance maintaining alveolar structural integrity [109], lung compliance, and oxygen exchange. It should be stressed that lung compliance, FEV1, FVC, and cardiopulmonary oxygen transfer are linearly related with physical performance [110]. Indeed, vitamin D induces the synthesis of alveolar surfactant and plays a critical role in epithelial-mesenchymal interactions during lung growth [111].…”
Section: Effects Of Vitamin D On Pulmonary Functionmentioning
confidence: 99%
“…These effects of vitamin D may be mediated through surfactant, a substance maintaining alveolar structural integrity [109], lung compliance, and oxygen exchange. It should be stressed that lung compliance, FEV1, FVC, and cardiopulmonary oxygen transfer are linearly related with physical performance [110]. Indeed, vitamin D induces the synthesis of alveolar surfactant and plays a critical role in epithelial-mesenchymal interactions during lung growth [111].…”
Section: Effects Of Vitamin D On Pulmonary Functionmentioning
confidence: 99%
“…16 We found that the mean FVC in athletes was significantly better (95.66%) compared to that of non-athletes (88.43%). Similarly, Vedala et al 17 and Mahotra 18 stated that the FVC in athletes was significantly higher than in non-athletes. Muscular exercise increases the rate and depth of respiration and improves FVC, the consumption of O 2 , and the rate of diffusion.…”
Section: Discussionmentioning
confidence: 90%
“…Exercise will make the durability and strength of respiratory muscles increase so that the lungs ability to expand also increases. Exercises help to improve respiratory muscle ability to overcome respiratory airflow resistance, which in turn increases air volume [16].…”
Section: B Differences Of Influence On High and Low Expiratory Peak mentioning
confidence: 99%